History, Location, and Species Matter: Insights for Human–Wildlife Conflict Mitigation From India. Issue 4 (4th July 2017) - Karanth, Krithi K.; Kudalkar, Sahila
ABSTRACT: Preventing loss of crops, threats to livestock, damage to property, and human injury and death attributed to wildlife are conservation challenges. We surveyed over 5, 000 households around 11 reserves in India to examine these issues and mitigation efforts. Crops were lost by 71% of households, livestock by 17%, and human injury and death were reported by 3% of households (losses attributed to 32 species). Households deployed 12 mitigation measures with nighttime watching, scare devices, and fencing used the most. A household's conflict history (>20 years for livestock loss, 10–20 years for crop loss), proximity to reserves, and crops grown or livestock owned were associated with higher mitigation use. There were differences across reserves, with households in Rajasthan least likely to use mitigation. Crop protection (88%) was more likely than livestock protection (32%). Investments in conflict mitigation should consider the history, location, species, socioeconomic variations among households, and differences in regional policies.